Estudio de factibilidad para la creación de una empresa consultora contable y tributaria en el cantón Mocache, año 2011 - Centeno Castro, Viviana Betzabeth (2012)
The idea of creating a company accounting and tax services for the Canton Mocache Los Rios province, is considered an opportunity to provide a development of technical, human and economic help for social and labor, as well as companies that require this type of service. Previous studies of market, technical, economic and financial evaluation, documented in the theoretical bibliographically helped develop this research study. The survey used in the research project yielded results that allowed us to know the needs of respondents, expressed through responses with a high percentage of acceptability by the population of Mocache The implementation, profitability and liquidity of Consulting demonstrated in the results of the economic and financial evaluation study that gave an Internal Rate of Return (IRR) with a percentage greater than two hundred percent to the cost of capital, a current value (NPV) greater than 1 and a cost-benefit ratio of 1.70, indicating that for every dollar invested returns 0.63 cents liquid. Within the methodology of research in the application of techniques and methods used in the present study the implementation of accounting and tax consulting relevant results are obtained and a substantial bibliographic compendium as query module for others. Mocache also showed that the implementation of projects needs to provide this type of service Accounting and Tax.